Jesuit Visual Culture and the Song nianzhu guicheng. The Annunciation as a Spiritual Meditation on the Redemptive Incarnation of Christ. (2nd January 2020) - Lopes (Universiti Brunei Darussalam), Rui Oliveira
Abstract: This paper examines the set of fifteen prints included in the seventeenth-century Chinese text Song nianzhu guicheng. This catechism was translated by Portuguese Jesuits serving in the China mission and consists of instructions for spiritual meditation on the fifteen mysteries of the Rosary. The processes of visual acculturation of Christian art will be examined in the context of the transmission of doctrine and instructions for spiritual meditation. The paper discusses the Chinese visual experience and the particular circumstances of the Catholic missions in China during and after the Nanjing persecutions. This paper demonstrates that although the illustrations of the Song nianzhu guicheng were executed and adapted by Chinese artists, the ontological principles of European Renaissance art and the precepts of Christian iconography are still a structural component in the Jesuit methods of teaching and preaching.